2019
DOI: 10.28932/jmh.v2i4.1841
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Lime (Citrus aurantifolia) Peel Extract in Preventing Biofilm Formation

Abstract: The routine and long term use of chemicals to maintain oral and dental health have the potency to result in the emergence of side effects; therefore another strategy is needed as an alternative such as using antimicrobial agents extracted from plants. The purpose of this study is to review the effectiveness of lime (Citrus aurantifolia) peel extract as an antibacterial in preventing biofilm formation. Biofilm is a component consisting of bacteria in a self-produced polymeric matrix, attached to an inert surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…This flavonoid acted by denaturing bacterial cell proteins so the bacterial cell wall destructed. The inhibition of glucosyltransferase (GTF) activity by the flavonoid can also help to prevent the formation of dental biofilm which is the main etiology of oral diseases such as caries and periodontitis [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This flavonoid acted by denaturing bacterial cell proteins so the bacterial cell wall destructed. The inhibition of glucosyltransferase (GTF) activity by the flavonoid can also help to prevent the formation of dental biofilm which is the main etiology of oral diseases such as caries and periodontitis [18].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that key lime also has an antibacterial effect against one of the bacteria that build the oral biofilm, Streptococcus mutans [16], [17], [18]. Streptococcus is one of the bacterial families that build the biofilm complex on oral surfaces along with around 700 other species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of essential oils as antimicrobial agents to inhibit microbial growth for high-quality and safe food production [5]. Because of the antibacterial activity contained in these compounds, so they can be used as natural antibacterial agents [6]. Limonene and other metabolites belonging to terpenoids, alkaloids, flavonoids, steroids, and cardiac glycosides be classified as Citrus spp.…”
Section: Introductionmentioning
confidence: 99%
“…6 Considering the 60 percent prevalence of dental caries among general population -which translates to 6 among 10 people, prevention should be prioritized as early as possible, the correct course would be to curtail the growth of Streptococcus mutans colonies. 7 Mechanical means such as simply brushing one's teeth could be used to prevent excessive Streptococcus mutans growth, and chemically, overthe-counter mouthwash is also effective. Traditional…”
Section: Introductionmentioning
confidence: 99%